Regulating the Sale and Consumption of Alcohol in Public Places in Malaysia - Dhina Dharshan Ganesan; Ramalinggam Rajamanickam; Mohd Zamre Mohd Zahir; Nur Khalidah Dahlan; Hasnizam Hashim; Mohd Safri Mohammed Na’aim (Veredas do Direito, 2026)
Non-Indexed Publication